Masking reveals parallel form systems in the visual brain - Lo, Yu Tung; Zeki, Semir (Frontiers in Human Neuroscience, 2014)
It is generally supposed that there is a single, hierarchically organized pathway dedicated to form processing, in which complex forms are elaborated from simpler ones, beginning with the orientation-selective cells of V1. In this psychophysical study, we undertook to test another hypothesis, namely that the brain’s visual form system consists of multiple parallel systems and that complex forms are other than the sum of their parts. Inspired by imaging experiments which show that forms of increasing perceptual complexity (lines, angles and rhombuses) constituted from the same elements (lines) activate the same visual areas (V1, V2 and V3) with the same intensity and latency (Shigihara and Zeki, 2013; 2014), we used backward masking to test the supposition that these forms are processed in parallel. We presented subjects with lines, angles and rhombuses as different target-mask pairs. Evidence in favour of our supposition would be if masking is the most effective when target and mask are processed by the same system and least effective when they are processed in different systems. Our results showed that rhombuses were strongly masked by rhombuses but only weakly masked by lines or angles, but angles and lines were well masked by each other. The relative resistance of rhombuses to masking by low-level forms like lines and angles suggests that complex forms like rhombuses may be processed in a separate parallel system, whereas lines and angles are processed in the same one.